Generation Z Employees in the Creative Industry: The Influence of Company Branding, Flexible Working Hours, and the Digital Work Environment on Company Attractiveness in Indonesia - Suwarna, A. Idun; Setiyawan, Agus; Kurniawan, Nur Hasan (West Science Interdisciplinary Studies, 2025)
This study examines the influence of corporate branding, flexible working hours, and the digital work environment on company attractiveness among Generation Z employees in Indonesia’s creative industry. Using a quantitative approach, data were collected from 120 respondents through a Likert-scale questionnaire and analyzed using SPSS version 25. The results reveal that all three independent variables—corporate branding, flexible working hours, and digital work environment—have positive and significant effects on company attractiveness. Corporate branding enhances organizational appeal by communicating authenticity, innovation, and credibility, while flexible working hours increase perceived freedom, trust, and work-life balance. The digital work environment emerges as the most influential factor, reflecting Generation Z’s strong affinity for technology-based collaboration and creativity. Collectively, these factors explain 51.6% of the variance in company attractiveness. The findings support employer branding and work design theories, demonstrating that organizational image, autonomy, and digital infrastructure jointly shape how young creative professionals perceive an ideal employer. Practically, the study emphasizes that creative industry organizations should strengthen brand identity, institutionalize flexible work arrangements, and enhance digital infrastructure to attract and retain Generation Z talent effectively.